Nursing students' perception of the effectiveness of problem based learning as a teaching/learning strategy to improve clinical decision making skills: A mixed method study [PowerPoint presentation] - Sealey-Tobias, Valerie; Jameson-Charles, Madgerie (My University, 2013)
An educational intervention utilizing problem-based learning (PBL) was introduced to teach the oncology module of a pathophysiology course for third-year nursing students at a School of Nursing in Trinidad and Tobago. This study describes those nursing students' perceptions of the effectiveness of PBL as a teaching/learning strategy. A proportionate random sampling method was used to select a sample of 30 nursing students from a population of 62 third-year nursing students who were exposed to the PBL sessions. A self-administered survey questionnaire with 10 quantitative and three qualitative questions was administered to the respondents, as well as a clinical decision-making test. Most of the students agreed that PBL caused a change in their thinking process. Their responses when categorized included themes such as enhanced critical thinking skills, better assessment skills, and information-gathering skills. All the students scored more than 50 percent in the clinical decision-making test, thus validating the students' perception that PBL had enhanced their clinical decision-making skills
Paper presented at the Biennial Conference of The University of the West Indies Schools of Education, 23-25 April, 2013, St. Augustine, Trinidad and Tobago
Keywords: Nursing students; Student attitudes; Perceptions; Problem-based learning; Educational strategies; Teaching techniques; Decision making; Clinical reasoning; Conference papers; Trinidad and Tobago